2011
DOI: 10.1111/j.1365-3164.2011.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus pseudintermedius exfoliative toxin EXI selectively digests canine desmoglein 1 and causes subcorneal clefts in canine epidermis

Abstract: Staphylococcal exfoliative toxins are known to digest desmoglein (Dsg) 1, a desmosomal cell-cell adhesion molecule, thus causing intraepidermal splitting in human bullous impetigo, staphylococcal scalded skin syndrome and swine exudative epidermitis. Recently, a novel exfoliative toxin gene (exi), whose sequence shares significant homology with previously identified exfoliative toxins, was isolated from Staphylococcus pseudintermedius. Little is known about the pathogenic involvement of this toxin in canine pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 42 publications
1
41
0
3
Order By: Relevance
“…Dogs injected with purified SIET developed lesions with positive Nikolsky's sign (exfoliation of skin when rubbed) with erythema and crusting which resemble those of canine pyoderma (104). On the other hand, other studies revealed that intradermal injection of recombinant SIET in dogs did not cause any lesions, either clinically or histopathologically (47). Thus, the biological significance of this toxin remains unclear (47,104,113).…”
Section: Staphylococcus Pseudintermediusmentioning
confidence: 99%
See 3 more Smart Citations
“…Dogs injected with purified SIET developed lesions with positive Nikolsky's sign (exfoliation of skin when rubbed) with erythema and crusting which resemble those of canine pyoderma (104). On the other hand, other studies revealed that intradermal injection of recombinant SIET in dogs did not cause any lesions, either clinically or histopathologically (47). Thus, the biological significance of this toxin remains unclear (47,104,113).…”
Section: Staphylococcus Pseudintermediusmentioning
confidence: 99%
“…The authors proposed the renaming of EXI as EXPA (exfoliatin of S. pseudintermedius type A), and the novel protein was named EXPB (exfoliatin of S. pseudintermedius type B). Moreover, it was shown that both EXPA and EXPB could digest canine desmoglein-1 (Dsg-1) and caused subcorneal splits in the epidermis when injected in mice, which resembles mechanisms involved in the pathogenesis of intraepidermal splitting in canine impetigo (46,47).…”
Section: Staphylococcus Pseudintermediusmentioning
confidence: 99%
See 2 more Smart Citations
“…Other diseases such as mastitis, arthritis, atopic dermatitis, inflammatory bowel disease, Kawasaki disease and autoimmune diseases have been associated with enterotoxins [11,12]. S. pseudintermedius exfoliative toxin SIET and exfoliative toxin EXI possibly play a role in the pathogenesis of cutaneous canine lesions and chronic otitis [13,14]. S. intermedius produces a bicomponent leukotoxin (Luk-I) similar to Panton-Valentine Leukocidin (PVL) of S. aureus, which is also encoded by two genes, LukS-I and LukF-I [15].…”
Section: Introductionmentioning
confidence: 99%